THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT TRIBE FIRE FIGHTING AND OFFICE SAVING SECTOR TAMANSARI JAKARTA BARAT - Ahmad Hidayat; Muhammad Mulyadi (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
The performance of employees in the fire prevention and rescue service is very important. Employee performance in firefighting and rescue service is influenced by the variables of Transformational Leadership Style and Work Environment. This research uses multiple linear regression analysis method approach. Samples were taken as many as 44 respondents. The Transformational Leadership Style variable has a significant influence on the Employee Performance variable of 16.5%, the Work Environment Variable has a greater influence on the Employee Performance variable than the Transformational Leadership Style variable of 23.5%. While the influence of the Transformational Leadership Style and the Work Environment together (simultaneously) has a significant influence on the Performance of the Fire and Rescue Service Sub-dept. of the West Jakarta Tamansari Sector Office by 29.5%.